PENGUATAN RESILIENSI SOSIAL MELALUI INOVASI PROGRAM LORONG WISATA DI KOTA MAKASSAR - Marta Suharsih; Muh. Iqbal Latief; Pratiwi Wulandari (Journal of Innovative and Creativity (Joecy), 2026)
This study focuses on strengthening social resilience through the innovation of the Tourism Alley (Lorong Wisata) program among alley communities in Makassar City. Empirical data and facts indicate that numerous social problems are evident in the daily lives of these alley communities. This study aims to: (1) analyze and describe the various social problems faced by Tourism Alley communities; (2) analyze the actionable policy measures required to strengthen social resilience among Tourism Alley communities; and (3) analyze the utilization of social groups in addressing social problems and strengthening social resilience within Tourism Alley communities. This research employs a qualitative method with a descriptive approach. Data sources comprise both primary and secondary data, collected through observation, in-depth interviews, focus group discussions (FGDs), and documentation. The data analysis technique used consists of data reduction, data display, and conclusion drawing/verification. The findings show that: (1) the social problems evident among Tourism Alley communities include poverty, inadequate infrastructure, sanitation and waste management problems, population density, potential criminality, social conflict among residents, limited involvement of local government, and institutional dependency on the Alley Council (Dewan Lorong); (2) the actionable policies required center on the structuring and revitalization of the Tourism Alley environment, economic empowerment of the community, and capacity strengthening of Tourism Alley communities, implemented through various program innovations; and (3) the utilization of social groups in the Tourism Alley program involving Posyandu (integrated health post) cadres, PKK (Family Welfare Movement) cadres, majlis taklim (Islamic study groups), and youth groups has not yet operated optimally. Social resilience among alley communities through the Tourism Alley program has begun to take shape, but it remains confined to the micro level, thus requiring intervention from multiple stakeholders to optimize it.